Análisis energético de un motor de combustión interna de encendido provocado bajo el uso de biocombustible obtenido a partir del mucílago de cacao - Muñoz Simi, Irene Milena (2022)
The objective of this project is to carry out an energy analysis of an ignition ICE using biofuel. The first phase is focused on obtaining the biofuel from cocoa mucilage, through fermentation and distillation processes; then the bioethanol is analyzed to determine its use as biofuel, then the characterization is performed, thus verifying the octane rating for use in ICE; with this, the behavior of this biofuel will be studied. The second phase of the project focuses on testing the selected vehicle, the Hyundai Grand i10 2020, on the selected route in the Sierra region, Conocoto parish, which has urban and extra-urban parts, making a comparison with two commercial fuels, Super and Extra. For the experimentation, measuring instruments are used to collect data for each route, performing two routes for each fuel. The data obtained from the CANedge equipment allows the calculations of power, fuel consumption, fuel mass flow, heat released by the engine, energy efficiency and exergy efficiency, while the CANmod allows the route to be plotted by GPS and the Skywatch collects the atmospheric parameters in which the experimental tests. The ICE is evaluated through the interpretation of characteristic curves such as power vs. RPM, fuel consumption vs. power, average energy efficiency and average exergetic efficiency of the fuels used for the experimentation. The analysis of the energy balance by ICE was represented by values in a table and in Sankey diagrams for each fuel that allows to appreciate how the energy is distributed in the vehicle system, thus defining the viability of the use of biofuel. Keywords: Energy analysis, Biofuel, Internal combustion engine (ICE), Energy efficiency, Exergetic efficiency.